The plague - Camus, Albert, 1913-1960
Chaos prevails when the bubonic plague strikes the Algerian coastal city of Oran. A haunting tale of human resilience in the face of unrelieved horror, Camus' novel about a bubonic plague ravaging the people of a North African coastal town is a classic of twentieth-century literature.
Winner of the Nobel Prize for Literature.
Translated from the French
Keywords: Disease Outbreaks -- Fiction; Epidemics -- Algeria -- Fiction; Plague -- Algeria -- Fiction